2012
DOI: 10.3892/etm.2012.478
|View full text |Cite
|
Sign up to set email alerts
|

The herbal medicine rikkunshito exhibits strong and differential adsorption properties for bile salts

Abstract: Abstract. Anti-secretory drugs, particularly proton pump inhibitors (PPIs), are the preferred treatment agents for patients with gastroesophageal reflux disease (GERD). However, refractory GERD, which may manifest as an incomplete or lack of response to PPI therapy, is common. Despite the administration of PPIs for symptomatic control, duodenogastroesophageal reflux (DGER) containing bile is successfully controlled in only one-third of patients. It has previously been reported that the traditional Japanese her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…It seems, however, that high doses of fish oil may adversely affect experimental colitis. Fiber sources have been reported to bind bile acids differently (39), which may affect development of colitis during a fish oil diet. The only study reporting a preventive effect for fish oil (33) used a purified diet containing cellulose, similarly to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It seems, however, that high doses of fish oil may adversely affect experimental colitis. Fiber sources have been reported to bind bile acids differently (39), which may affect development of colitis during a fish oil diet. The only study reporting a preventive effect for fish oil (33) used a purified diet containing cellulose, similarly to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…25 Araki et al reported that rikkunshito strongly absorbed hydrophobic bile salts. 26 As hydrophobic bile salts are known to induce oxidative stress and inflammation in the upper gastrointestinal tract, decreased levels of these might improve visceral hypersensitivity in the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Araki et al showed that RKT can potently absorb bile salts [23]. In addition, RKT improved acid regurgitation-associated signs through prevention of both decreases in the tight junction protein and increases in the intercellular space of the epithelial mucosa in a rat reflux esophagitis model [24].…”
Section: Discussionmentioning
confidence: 99%